2013
DOI: 10.1007/s10067-013-2430-0
|View full text |Cite
|
Sign up to set email alerts
|

WHO-ILAR COPCORD study (stage 1, urban study) in Sanandaj, Iran

Abstract: This study aims to conduct an urban Community Oriented Program for Control Of Rheumatic Diseases (COPCORD) study in Sanandaj (Kurdistan, Iran). Sanandaj with a population of 311,446 (2006 census), Caucasian of Kurdish subgroup, was selected as the field. Sanandaj was divided into 100 clusters and subjects were randomly selected from them (50 subjects from each cluster). The COPCORD study started on July 2011 and ended on June 2012. Of the households, 1,631 was visited and 5,830 persons were interviewed. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 20 publications
4
46
3
1
Order By: Relevance
“…In other words, both musculoskeletal manifestations were almost two times more prevalent in diabetic patients. On the other hand, the prevalence of the most common musculoskeletal manifestations in the general population of Iran found by the Community Oriented Program for Control of Rheumatic Diseases (COPCORD) study were knee osteoarthritis, rotator cuff tendinitis and CTS (Table ) . The selected COPCORD studies represented almost all ethnic groups of urban populations in Iran.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, both musculoskeletal manifestations were almost two times more prevalent in diabetic patients. On the other hand, the prevalence of the most common musculoskeletal manifestations in the general population of Iran found by the Community Oriented Program for Control of Rheumatic Diseases (COPCORD) study were knee osteoarthritis, rotator cuff tendinitis and CTS (Table ) . The selected COPCORD studies represented almost all ethnic groups of urban populations in Iran.…”
Section: Discussionmentioning
confidence: 99%
“… †Reference ; ‡Reference ; §Reference . COPCORD, Community Oriented Program in the Rheumatic Diseases. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on poloxamine 908 coating polystyrene nanospheres revealed a reduction of fibronectin adsorption compared to uncoated nanospheres [63]. Coating of both singlewalled carbon nanotubes and amorphous silica particles with Pluronic F127 resulted in the enhancement of dispersion of the NPs but notably decreasing adsorption of serum proteins [64].…”
Section: Effect Of Surface Functional Group and Coatingmentioning
confidence: 99%
“…It has a high prevalence in Asian countries (from 4.1% to 11.3%), 1 especially in Iran (from 16% to 21%). [2][3][4][5][6] Unfortunately, the available treatments are more symptomatic than preventive. Although some of them may slow down the process, there is no hope for a reversal, leading gradually to more cartilage loss and finally to joint replacement.…”
Section: Introductionmentioning
confidence: 99%